An Integrative Review of Carers' Perceptions of Seclusion and Restraint in Mental Health Care: A Critical Appraisal and Call for Methodological and Conceptual Precision...Hawsawi T, Appleton J, Sheppard LS, et al. Carers’ Perceptions of Seclusion and Restraints in Mental Healthcare: An Integrative Literature Review. International Journal of Mental Health Nursing. 2025;34(6):1-18. - Mei, Wang; Lixia, Li; Jinhuan, Wang; Jiachun, Wang (International Journal of Mental Health Nursing, 2026)
The article focuses on an integrative review concerning carers' perceptions of seclusion and restraint (S/R) in adult mental healthcare, highlighting the importance of including carers' voices in discussions about these practices. It emphasizes the trauma experienced by carers and their demand for meaningful involvement in care, while also critiquing the review's methodological and conceptual shortcomings. The authors argue for a more rigorous approach to synthesizing qualitative and quantitative data and call for clearer definitions of terms like "least coercive measure" and "last resort" to prevent misuse in practice. They advocate for a shift towards developing non-coercive alternatives in mental health care, informed by carers' insights.